Comparison of three decontamination methods for Mycobacterium bovis isolation - Ambrosio,Simone Rodrigues (2008)
Sixty samples of tissue fragments with lesions suggestive of tuberculosis from bovine abattoirs, kept in saturated solution of sodium borate, were subjected to four treatments: 4% NaOH (Petroff Method), 12 % H2SO4 and 1.5% HPC (1-Hexadecylpyridinium Chloride) decontamination, and physiological saline solution (control). The HPC method showed the lowest contamination rate (3%) when compared to control (88%, p<0.001), NaOH (33%, p<0.001) and H2SO4 (21.7%, p<0.002). Regarding the isolation success, the HPC method was better (40%) than the control (3%, p<0.001), NaOH (13%, p=0.001) and H2SO4 (1.7%, p<0.001) methods. These results indicate that HPC is an alternative to the Petroff method.